The Right to Housing of The Female Devose at The in Islamic Thinking and Iraqi Law - Faris Ali Mustafa (QALAAI ZANIST SCIENTIFIC JOURNAL, 2022)
This study will explain (The dsnt giveing housing of the female devose at the in Islamic thinking and Iraqi law. The right to housing is one of the rights in rem branching right of ownership is a right entitles the owner and his family residential property owned by the non-was organized by the Iraqi legislature in articles 1261 - 1265 of the Civil Code of Iraq, but the law of real estate registration was organized by the making is the possibility of arranging impossible on the ground so that the dispositions contained a drug is known as negligible what were not registered in circles Date property and the latter to refrain from registration for failure to regulate the procedures for registration in the law has focused research on the study of the right kind beginner defined and stand at the characteristics and the statement of the reasons for his earnings and then see its effects and methods expiry to end a set of findings and recommendations which we found that they can deal with what is going on the subject of al legislative missing or modification of an existing legislative situation.